POPULATION HEALTH AND HEALTH SERVICES: OLD CHALLENGES AND NEW REALITIES IN THE COVID-19 ERA - Sarría-Santamera, Antonio; Yeskendir, Alua; Maulenkul, Tilektes; Orazumbekova, Binur; Gaipov, Abduzhappar; Imaz-Iglesia, Iñaki; Pinilla-Navas, Lorena; Moreno-Casbas, Teresa; Corral, Teresa (Int. J. Environ. Res. Public Health, 2021)
Health services that were already under pressure before the COVID-19 pandemic to maximize its impact on population health, have not only the imperative to remain resilient and sustainable and be prepared for future waves of the virus, but to take advantage of the learnings from the pandemic to re-configure and support the greatest possible improvements. (2) Methods: A review of articles published by the Special Issue on Population Health and Health Services to identify main drivers for improving the contribution of health services on population health is conducted. (3) Health services have to focus not just on providing the best care to health problems but to improve its focus on health promotion and disease prevention. (4) Conclusions: Implementing innovative but complex solutions to address the problems can hardly be achieved without a multilevel and multisectoral deliberative debate. The CHRODIS PLUS policy dialog method can help standardize policy-making procedures and improve network governance, offering a proven method to strengthen the impact of health services on population health, which in the post-COVID era is more necessary than ever
Keywords: Type of access: Open Access; delivery of health care 2; health service; preventive 3; health promotion 4; health policy